Perencanaan Persediaan Bahan Baku Biji Kopi Menggunakan Metode Min dan Max Pada UMKM Deli Coffee - Zaharuddin, Zaharuddin; Marisden, Giat Damei; Walady Utama, Denny; Meuthia Hasibuan, Yetti (Fakultas Teknik UMRI, 2026)
Inventory of raw materials is something that must be considered. In order for a production process to run smoothly, the company must have a good supply of raw materials so that production continues and demand can be met. Inventories are stored materials or goods that will be used to fulfill certain purpose. Focusing on small and medium enterprises (SMEs) which are included in the food and Baverage business category. Deli Coffee UKM which produces various types of coffee beans. Ordering raw materials made by SMEs is still relatively unplanned. Orders are made when there is a small supply of materials in the warehouseand orders from suppliers and 15 days for new orders to arrive. Data collection methods used are primary and secondary data. Min-max supply chain of coffee beans for safety stock is 151, 93 kg, minimum inventory of 223,59 kg, maximum inventory of 4283,33 kg, and reorder point of 1989,74 kg and order quantity per period of 223 order frequency of 11 times, and total cost of IDR 8.375.642.000.